MRI OF ADRENAL DISEASES AND STOMACH CANCER (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2023)
The genuine interest of a number of medical specialists, such as therapists, endocrinologists, oncosurgeons and radiology specialists, in diseases is due, first of all, to their prevalence, diversity and often similarity of clinical picture, as well as the complexity of diagnosis.